Evaluation of the therapeutic effects of Artemisia absinthium L. on pseudopregnancy model in rats - Demirel, Murside Ayse; Suntar, Ipek; Ceribasi, Songul; Zengin, Gokhan; Ceribasi, Ali Osman (Springer, 2018)
Researchers have been investigating new treatment strategies for the management of pseudopregnancy, due to some long term causes of this disease including mastitis and mammary tumor. Owing to the side effects of hormone therapy, much attention has been focused on more tolerable treatment options including natural remedies. In the present study, we aimed to investigate the therapeutic effects of Artemisia absinthium L. (wormwood) on pseudopregnancy model in rats. A. absinthium, which is a perennial shrubby plant from Asteraceae family, was reported to be used as an emmenagogue in folk medicine and was previously shown to modulate dopaminergic system. In the present study, pseudopregnancy model was induced in female Sprague-Dawley rats by injection of pregnant mare's serum gonadotropin and human chorionic gonadotropin. The petroleum ether, dichloromethane and methanol extracts of A. absinthium, prepared by successive extraction method, were orally administered to the rats at 100 mg/kg dose, once daily for 10 days. Bromocriptine (3 mg/kg/per os) was administered to the reference group animals. At the end of the experiment, all of the animals were sacrificed, the blood samples, ovaries and uterine tissues were taken for histopathological and biochemical analysis. According to the results of the present study, the petroleum ether extract displayed beneficial effects in pseudopregnancy model in rats when compared with the control group. Therefore, Gas Chromatography analysis was conducted on this extract to reveal its phytochemical profile.
Phytochemical-Society-of-Europe Symposium on New and Old Phytochemicals - Their Role in Ecology, Veterinary and Welfare -- SEP 17-20, 2017 -- Chieti, ITALY
Keywords: Asteraceae; Artemisia absinthium; Dopaminergic; Pseudopregnancy; Rat